Psychological Analysis On Freud’s Personality Theory On Popov And Smirnov’s Dynamic Characters As Seen In The Bear By Anton Chekov - Insan Kamil Tatubeket (Jurnal Ilmiah Langue and Parole, 2017)
The Bear is a literary work written by anton chekov in 1880 which tells of the story of a widow who dissolves in sorrow after being dying by a beloved husband who then personality or his formerly gentle, polite nature turned into a rough and grumpy as being carried away with a collector Harsh debt but turned into a romantic and gentle. Changes in attitudes that occur to the store antagonist and protagonist caused by loneliness and needs that harbor the sense of mutual need that in the end both are equally in love.